Chondrogenic differentiation of mesenchymal stem cells in a hydrogel system based on an enzymatically crosslinked tyramine derivative of hyaluronan - Dvořáková, Jana; Kučera, Lukáš; Kučera, Jan; Švík, Karol; Foglarová, Marcela; Muthný, Tomáš; Pravda, Martin; Němcová, Miroslava; Velebný, Vladimír; Kubala, Lukáš (Journal of biomedical materials research. Part A, 2014)
Hyaluronan-based tissue substitutes are promising materials in cartilage reconstruction surgery. Herein, the chondrogenesis of human mesenchymal stem cells (MSC) in a hydrogel based on a tyramine derivative of hyaluronan crosslinked by hydrogen peroxidase (HA-TA) was evaluated. Human MSC seeded in the scaffold were incubated in standard chondrogenic medium and medium enriched with bone morphogenetic protein-6 (BMP6). Cell viability, the gene expression of selected markers (collagen type II, aggrecan, SOX9, collagen type X, and osteopontin), and the histological characteristics were examined during three weeks of in vitro cultivation. The tissue reaction of both unseeded and MSC seeded HA-TA scaffolds were tested in vivo after subcutaneous application in rats for 12 weeks. The data showed that cells resisted the process of crosslinking and remained viable for the whole time while exhibiting changes in cell organization. Human MSC cultivated in HA-TA hydrogel expressed genes of both chondrogenic and osteogenic differentiation and the addition of BMP6 revealed a tendency to potentiate both processes. Histological analysis of HA-TA in vivo implants did not reveal a chronic inflammatory reaction. In both cases, in vivo HA-TA implants were continuously degraded and MSC-seeded hydrogels tended to form clusters similar to in vitro samples. In conclusion, MSC chondrogenic differentiation may proceed in a HA-TA scaffold that is biocompatible. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3523-3530, 2014.
Keywords: Subcutaneous Tissue; lidé; Tyramine; reagencia zkříženě vázaná; Gene Expression Regulation; Hyaluronic Acid; krysa rodu Rattus; Cell Survival; experimentální implantáty; Humans; Cells, Immobilized; peroxidasa; chondrogeneze; Hydrogel, Polyethylene Glycol Dimethacrylate; Mesenchymal Stem Cells; buněčná diferenciace; tyramin; viabilita buněk; zvířata; Implants, Experimental; zobrazování trojrozměrné; Rats; mezenchymální kmenové buňky; Animals; Imaging, Three-Dimensional; PEG-DMA hydrogel; regulace genové exprese; Cell Differentiation; imobilizované buňky; kyselina hyaluronová; subkutánní tkáň; Peroxidase; Cross-Linking Reagents; Chondrogenesis